2023
DOI: 10.1021/acscatal.3c02648
|View full text |Cite
|
Sign up to set email alerts
|

Transition-State Stabilization by Secondary Orbital Interactions between Fluoroalkyl Ligands and Palladium During Reductive Elimination from Palladium(aryl)(fluoroalkyl) Complexes

Eric D. Kalkman,
Yehao Qiu,
John F. Hartwig

Abstract: Palladium-catalyzed fluoroalkylations of aryl halides are valuable reactions for the synthesis of fluorinated, biologically active molecules. Reductive elimination from an intermediate Pd(aryl)(fluoroalkyl) complex is the step that forms the C(aryl)− C(fluoroalkyl) bond, and this step typically requires higher temperatures and proceeds with slower rates than the reductive elimination of nonfluorinated alkylarenes from the analogous Pd(aryl)(alkyl) complexes. The experimental rates of this step correlate poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Oxidative addition is computed to be rate-determining because the differences in energies between TS RE ‡ -a–c and [Cu]-3-a–c , respectively, are smaller than the differences between TS OA ‡ -a–c and [Cu]-3-a−c for each of the fluoroalkyl groups investigated. Our group has previously identified by computation a stabilizing interaction between the palladium center and the nitrile CN bond during reductive elimination from a phosphine-ligated fluoroalkyl–arylpalladium complex; however, we did not identify an analogous stabilizing interaction between the copper center and the nitrile CN bond in [Cu]-3-a−c using an independent gradient model based on Hirschfield partitions (IGMH analysis) …”
Section: Resultsmentioning
confidence: 63%
“…Oxidative addition is computed to be rate-determining because the differences in energies between TS RE ‡ -a–c and [Cu]-3-a–c , respectively, are smaller than the differences between TS OA ‡ -a–c and [Cu]-3-a−c for each of the fluoroalkyl groups investigated. Our group has previously identified by computation a stabilizing interaction between the palladium center and the nitrile CN bond during reductive elimination from a phosphine-ligated fluoroalkyl–arylpalladium complex; however, we did not identify an analogous stabilizing interaction between the copper center and the nitrile CN bond in [Cu]-3-a−c using an independent gradient model based on Hirschfield partitions (IGMH analysis) …”
Section: Resultsmentioning
confidence: 63%
“…NPA analysis could also help evaluate intra- and intermolecular interactions and estimate the strength of the coordination interaction of the metal palladium and the ligand. 62 Herein, we carried out a second-order perturbation analysis of the NBOs on transition states TS1a , TS3a , and TS4a (Table S2†). In transition state TS4a , the sum E (2) values of d → n*, σ → d*, and n → d* interactions between Pd and CC (olefin) as well as the MeO − group is 127.6 kcal mol −1 , which is larger than d → π* of Pd⋯CC (olefin) in TS1a (24.4 kcal mol −1 ) and d → π*, σ → d*, and n → d* in TS3a (71.6 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This variation further confirmed that the coordination environment of the metal center changes from the Pd-P double coordination model to NPA analysis could also help evaluate intra-and intermolecular interactions and estimate the strength of the coordination interaction of the metal palladium and the ligand. 62 Herein, we carried out a second-order perturbation analysis of the NBOs on transition states TS1a, TS3a, and TS4a (Table S2 † Moreover, the substrate oxindole provides the n → σ* interaction between O1 and H2 to stabilize the TS4a structure, which is absent in TS1a and TS3a. Therefore, the cooperative action of the phosphine ligand, the double bond on the substrate isoprene, MeOH, and the palladium catalyst were found to be crucial for the preferential ΔG ‡ value of TS4a.…”
Section: Reaction Mechanisms For Reaction I With a Bidentate Phosphin...mentioning
confidence: 99%